Daily field checking list by Walter Rosene, March 10, 1937 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed in Boone County by Walter Rosene and Bob Walker, March 10, 1937. Also notes the eggs in the Great Horned Owl nest have not yet hatched. Plustek--flatbed